Investigative and laboratory assays for allogeneic rejection – A clinical perspective - Xin Jiang; Qiang Sebastian Shi; Cheng-Yu Wu; Lu Xu; Hongji Yang; MedhatAskar (Transplantation Reports, 2023)
How to translate basic research on surveillances for post organs transplantation facilitates the development of new laboratory tools for clinical application. Here, we provide the pertinent guide on how to analyze laboratory data in order to help clinicians to accurately determine the status of allograft in the recipient. We begin by discussing the molecular and cellular events that lead to allograft rejection across innate and adaptive immune responses. We focus on the allograft injury events that occur around the time of transplantation as well as molecular activities that ensue long before observable microscopic abnormalities are evident in biopsied samples. Then, we introduce and comment on new technologies involved in rejection detection from a practical point of view. This review outlines the current diagnostic development, describes unmet needs and challenges, and proposes new approaches for future directions.